UJI PERBANDINGAN PAKAN PELLET DAN CUMI-CUMI TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP BENIH IKAN KERAPU MACAN (Efinephelus fuscoguttatus) - Jerri H; Muhamad Agus; Komariyah . (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2014)
Tiger grouper fish commonly known as "groupers" and it is the one commodity that has domestic and international market opportunities. Purpose of this study is to determine the effect of different feeding pellets and squid on the growth and survival of tiger grouper  (Epinephelus fuscoguttatus). The study was carried out on April 25th, 2014 until May 24th, 2014 in Hatchery home scale, Saga vilage, District of  Tanjungpandan,  Belitung  province.  The  experimental  design  in  this  study  is  using  a  complete randomized  design  (CRD)  with  2  treatments  and  4  replicates,  they  are  treatment  A  (pellets)  and treatment  B  (squid).  Result  shows  the  highest  average  weight  gain  of  biomass  tiger  grouper  seed obtained  on  treatment  A  (pellets)  biomass  weight  gain  is  16.18  grams  and  survival  100%,  whereas treatment B (squid) the biomass weight gain 11.53 grams and survival 85%. The results of t test step, note that the value of T count is greater than the T table which means the ratio of feed pellets and squid provide  highly  significant  influence  on  the  growth  and  survival  of  seed  tiger  grouper  (Epinephelus fuscoguttatus). Water quality maintenance media for research is still at a decent range of temperature is from 27.5-30°C, pH 7.6 - 8, and dissolved oxygen 3.4-5.4 ppm.  Key Words: tiger grouper, growth, survival rate, feed